Scenarios for a 2 °C world: a trade-linked input–output model with high sector detail. (2nd April 2016) - De Koning, Arjan; Huppes, Gjalt; Deetman, Sebastiaan; Tukker, Arnold
Abstract : In this study a scenario model is used to examine if foreseen technological developments are capable of reducing CO2 emissions in 2050 to a level consistent with United Nations Framework Convention on Climate Change (UNFCCC) agreements, which aim at maximizing the temperature rise to 2 °C compared to pre-industrial levels. The model is based on a detailed global environmentally extended supply–use table (EE SUT) for the year 2000, called EXIOBASE. This global EE SUT allows calculating how the final demand in each region drives activities in production sectors, and hence related CO2 emissions, in each region. Using this SUT framework, three scenarios have been constructed for the year 2050. The first is a business-as-usual scenario (BAU), which takes into account population, economic growth, and efficiency improvements. The second is a techno-scenario (TS), adding feasible and probable climate mitigation technologies to the BAU scenario. The third is the towards-2-degrees scenario (2DS), with a demand shift or growth reduction scenario added to the TS to create a 2 °C scenario. The emission results of the three scenarios are roughly in line with outcomes of typical scenarios from integrated assessment models. Our approach indicates that the 2 °C target seems difficult to reach with advanced CO2 emission reduction technologies alone. Policy relevance The overall outlook in this scenario study is not optimistic. We show that CO2 emissions from steel and cement production and air and sea transport will become dominant in 2050. They are difficult to reduce further. Using biofuels in air and sea transport will probably be problematic due to the fact that agricultural production largely will be needed to feed a rising global population and biofuel use for electricity production grows substantially in 2050. It seems that a more pervasive pressure towards emission reduction is required, also influencing the basic fabric of society in terms of types and volumes of energy use, materials use, and transport. Reducing envisaged growth levels, hence reducing global gross domestic product (GDP) per capita, might be one final contribution needed for moving to the 2 °C target, but is not on political agendas now.